Pengembangan Lembar Kerja Peserta Didik (LKPD) Polimer Sintetis dan Karbohidrat Berbasis Problem Based Learning Untuk Kelas XII SMA/MA - Farizka, Widya (RC-INSTITUT, 2019)
Actually these material has been applying in students daily life. The students could be given a problem in learning process that related to reality. The correct model can be used is Problem Based Learning. The research purpose is to make student worksheets (LKDP) based on problem in polymer and carbohydrate material. This research use 4-D to find the validation, there are 4 steps; (1) define (2) design (3) develop and (4) disseminate but in this research only use until develop step. Instrumentations are questioner validity that filled by lecture and teacher, questioner practicalities is filled by students in SMA Pembangunan Laboratorium UNP. Data from this research will be analyzed using Cohen’s kappa formula. Based on the analysis of questionnaire known that LKPD produced has a very high validity category (κ=0,88) very high practicalities (κ=0,97) based on teacher judgement; and high practicalities (κ=0,94) based on student judgement. Keywords: Student Worksheets, Problem Based Learning, Polymer Syntetic, carbohidrat, Research and Development, 4-D Model